Top 100 most-cited articles on hemorrhoids: A bibliometric analysis and visualized study - Wang, Zhaochu; Wu, Xuxiong; Li, Yang; Huang, Juan; Shi, Rong; Wang, Jing (Frontiers in Surgery, 2022)
Background Hemorrhoids have a significant incidence in people and are becoming a common public health problem. This study provides a bibliometric and visualized analysis of the most influential literature in the field. The aim is to reveal trends in the field of hemorrhoids and to provide a reference for researchers. Methods The 100 most frequently cited studies in the field of hemorrhoids were collected from the Web of Science(WOS), and were analyzed in terms of the annual publication, types of literature, countries, institutions, authors, journals, and keywords. During the study, we used a combination of VosViewer, Carrot2, Microsoft Excel, and Tableau tools to better present the visual information. Results A total of 4,481 articles were retrieved, of which 3,592 were of the Article and Review types, among which we selected the 100 most frequently cited. A large amount of highly cited literature on hemorrhoid surgery emerged from 1990 to 2010, and the interest of researchers in hemorrhoid surgery seems to have waned after 2010. The sources of highly cited literature in the field of hemorrhoids are predominantly Western, with the United States. and the United Kingdom accounting for almost half of the publications worldwide. However, countries with higher prevalence populations do not have significant research on hemorrhoids. St. Mark's Hospital has published the largest number of influential articles in the field of hemorrhoid disease. Kamm MA and Phillips RKS are the most authoritative authors in the field. Diseases of the Colon & Rectum and the British Journal of Surgery are the most influential journals in this field. The highly cited literature covers a wide range of disciplines, with Thomson's classic “The nature of hemorrhoids” receiving the most attention among the studies focusing on hemorrhoids. Keyword and clustering analysis revealed that The most famous focus in the field of hemorrhoid research is the evolution of stapled hemorrhoidectomy (SH) and Milligan-morgan hemorrhoidectomy (MMH). Conclusions This study is the first to explore developments in the field of hemorrhoids, and it helps surgeons quickly understand global trends in the field of hemorrhoids. In recent years, the development of hemorrhoids seems to have hit a bottleneck, with scholarly interest in the field of waning, especially in surgery Procedures. The theory of inferior anal cushion migration has proven to be the most influential theory in the field, but after studies based on SH and MMH, more high-quality evidence is needed to continue advancing the field of hemorrhoids. The results of this study are intended to add to the attention and interest of scholars in this area and provide a reference for further research.